Phytochemical compounds, vitamin C levels, and antioxidant activity of soursop leaves (Annona muricata Linn) tea powder under various drying durations. - Fitrasyah, Siti Ika; Ningsih, Srirahayu; Rahman, Nurdin; Rakhman, Aulia; Ariani, Ariani; Aiman, Ummu (Nutrición Clínica y Dietética Hospitalaria, 2025)
Introduction: Soursop leaves (Annona muricata Linn) possess numerous properties that play a significant role in preventing various diseases, such as antibacterial, antioxidant, anticancer, anti-inflammatory activities, and their ability to act as immunomodulators. Degenerative diseases are primarily caused by the harmful effects of free radicals. Oxidative stress induced by free radicals leads to various degenerative diseases that can damage the body. Antioxidants mitigate this by donating electrons to free radicals, thereby playing a crucial role in the body’s defense mechanisms. Aim: This study aims to analyze the phytochemical compounds, vitamin C levels, and antioxidant activity of soursop leaf tea powder under varying drying durations. Methods: This quantitative research employed a descriptive design based on laboratory testing. Phytochemical compounds were analyzed qualitatively, vitamin C levels were measured using the titration method, and antioxidant activity was determined using Ultra Violet-Visible (UV-Vis) Spectrophotometry with the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. A one-way Analysis of Variance (ANOVA) was used for statistical analysis, as the data obtained followed a normal distribution. Results: The results revealed that all samples tested positive for phytochemical compounds, including flavonoids, saponins, tannins, alkaloids, and terpenoids. A significant effect of drying duration variations on vitamin C levels and antioxidant activity was observed, with a p-value < 0.05. Conclusion: In conclusion, soursop leaves are a promising source of natural bioactive compounds, with drying at 50°C for 3 to 6 hours effectively preserving vitamin C content and enhancing antioxidant activity. However, extending the drying time to 12 hours may lead to a slight reduction in these beneficial properties. Statistical analyses confirm that drying time significantly affects both vitamin C levels and antioxidant activity in soursop leaf tea powder.